Evaluation in education: the need of institutional policies with pedagogical vision - Torres Zambrano, Manuel Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2011)
Educational evaluation has frequently been characterized for being more about isolated and instrumental acts, than about the possibility of pedagogical development, hence it is not supported in policies and explicit concepts. In order to look for alternative paths to this situation, this paper begins with a revision of evaluation practices and draws up questions aimed at discovering what is the role of evaluation in the educational context, and in relation to the aims of education. Later, it explores the role of educational policies, in order to assert the necessity of having grounded evaluation policies that provide opportunities that can achieve developments in evaluation, while contributing in a significant way to educational improvement. The discussion concludes with a set of guidelines for formulating evaluation policies and making those policies operational.